Idiopathic granulomatous cheilitis of Miescher in a young patient: A rare entity and its successful treatment - Asha Gowrappala Shanmukhappa; Bhumika Shivaram; Leelavathy Budamakuntala; Archana Samynathan (Wolters Kluwer Medknow Publications, 2017)
Granulomatous cheilitis (GC) of Miescher is a chronic inflammatory disorder of unknown etiology affecting young adults, characterized by asymptomatic, unrelenting swelling of lips. An array of treatment modalities have been tried, only for the disease to recur again. We report a case of GC with significant remission after treatment with a combination of steroids, metronidazole, and doxycycline. There were no signs of relapse at 6 months of follow-up.